An evocative portrayal of stay-at-home-dads' experiences in elementary schools through poetic inquiry. Issue 4 (2nd October 2019) - Haberlin, Steve; Davis, Eric
ABSTRACT: In this article, we embraced poetic inquiry to evocatively represent the experiences of stay-at-home dads (SAHDs) with children in elementary schools. We argue that traditional qualitative research methods may not capture the emotionality inherent within SAHD research, and thus, produce new meaning and insight into a commonly studied topic. We crafted three found poems from interview transcripts derived from a larger study involving 14 stay-at-home fathers and their experiences, including interactions at their children's schools. The poems are followed by analytical interpretations. Implications include emphasizing the representation of qualitative data, using poetic inquiry to investigate the affective domain of SAHDS, and using poetry research in assisting school employees to understand challenges faced by SAHDs.